HOMESICK : June 5 - June 29 - Bartana, Yael (2025)
Location: Wasserturm Prenzlauer Berg Entry from: Diedenhofer Str. 6, 10405 Berlin Homesick is the first exhibition dedicated entirely to the artist’s three decades of neon art. Her unique poetic electric signs will illuminate the haunted and magical underground space of the Wasserturm in Berlin.
Keywords: Homesick; Neon; Wasserturm; Berlin; FramedFest2025